2016
DOI: 10.1007/s13280-016-0783-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-fledging movements of white-tailed eagles: Conservation implications for wind-energy development

Abstract: The presence of poorly sited wind farms raises concerns for wildlife, including birds of prey. Therefore, there is a need to extend the knowledge of the potential human-wildlife conflicts associated with wind energy. Here, we report on the movements and habitat use of postfledging satellite-tagged white-tailed eagles in Finland, where wind-energy development is expected to increase in the near future. In particular, we examine the probability of a fledgling approaching a hypothetical turbine that is placed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Increasing knowledge about risks associated with wind farms encouraged the Finnish WTE working group and WWF Finland to compile guidelines for eagle-safe wind farm construction (Nuuja 2017). Telemetry study of dispersing juveniles showed that risks can be reduced by avoiding construction of wind turbines along the coastline and with a 2 km buffer zone between WTE nests and turbines (Balotari-Chiebao et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing knowledge about risks associated with wind farms encouraged the Finnish WTE working group and WWF Finland to compile guidelines for eagle-safe wind farm construction (Nuuja 2017). Telemetry study of dispersing juveniles showed that risks can be reduced by avoiding construction of wind turbines along the coastline and with a 2 km buffer zone between WTE nests and turbines (Balotari-Chiebao et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only Balotari‐Chiebao et al . (2016) primarily described spatial aspects of post‐fledging movements of WTSE in detail, yet no quantitative assessment of excursive behaviour and related interplay with the onset of dispersal currently exists.…”
Section: Introductionmentioning
confidence: 99%
“…These resulting circular areas were our study areas. Further details on the space use and ranging behaviour of the study eagles can be found in Balotari-Chiebao et al (2016a).…”
Section: Study Areasmentioning
confidence: 99%
“…These include nest-site selection in reintroduced (Evans et al 2010), naturally returning (Treinys et al 2016) and recovering populations (Radović and Mikuska 2009;Sándor et al 2015). Other studies have focused on individual movements with high-precision telemetry data to study home ranges and habitat use (Scholz 2010;Krone et al 2013;May et al 2013;Balotari-Chiebao et al 2016a;Bragin et al 2018). However, the post-fledging period, defined as the period between fledging and dispersal from the natal area (Morrison and Wood 2009), has generally received less attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation